(untitled) (Quinto Sol, 2013)
The aim of this paper is to contribute to the characterization of the rioplatense rural world in the first half of the nineteenth century by the analysis of the colonization process in an area situated in the south of Salado River in present Buenos Aires province. We circumscribe our work in time and space focusing on Dolores District (with a larger surface than the present one) between 1879 and 1860. The characterization of the process to access to the usufruct and to the legal property of land in the area added to the social and demographical analysis of the population (Mascioli,1999) expects to be a contribution to the above mentioned topic. The case studied is far from being a paradigmatic example of the “expansion of livestock breeding” that would have taken place in latifundia owned by a few owners (a familiar image when we talk about an area situated in the south of Salado River in times of the colonization process between the end of the eighteenth century and the beginiing of the nineteenth century). The complexity and dynamism of the process studied are evident: to usufruct and to access to the legal property of land in Dolores implies the possibility to transit different ways for producers with different posibilities and necessities. Besides, the reconstruction of the process will let us compare it with others that took place in other lands and time, in order to explain the occupation of the pampeano surface in a diachronic perspective.